The effect of automated accounting systems (AAS) on audit independence: Empirical Evidence from South West, Nigeria. - Amos Olusola AKINOLA; Adekunle Olusola OLADEJO; Ebenezer Foluso OLUWAKAYODE; Abud-Azeez Adetunji ADEREMI (Eurasian Journal of Management & Social Sciences)
This study examines the effect of an automated accounting system (AAS) on the audit independence of external auditors in South-West, Nigeria. A cross-sectional survey design with primary data sourced through a structured questionnaire drawn on four Likert scales and a total of 514 copies of the questionnaire physically/virtually administered to auditors (randomly selected) in private engagement in six states of South West, Nigeria.  362 valid questionnaires were descriptively analysed using percentages and mean. Also, inferential statistics were applied with multiple regression analysis. The findings show that there are positive significant effects of AAS on program, investigative, and reporting independence. Furthermore, it reveals that there is a positive significant effect of AAS on independent in fact of external auditors. It is therefore recommended that private and public entities should embrace automation of accounting functions as this redresses the incidence of familiarity and direct interference with the audit process by clients (auditees).